Employability as a Guiding Outcome in Veterinary Education: Findings of the VetSet2Go Project - Cake, Martin; Bell, Melinda; Cobb, Kate; Feakes, Adele; Hamood, Wendy; Hughes, Kirsty; King, Eva; Mansfield, Caroline F.; McArthur, Michelle; Matthew, Susan; Mossop, Liz; Rhind, Susan; et al. (Frontiers in Veterinary Science, 2021)
This paper presents a mini-review of employability as a guiding outcome in veterinary education – its conceptualisation, utility, core elements and dimensions, and pedagogical approaches – through a summary of the findings of a major international project with the same aims (the VetSet2Go project). Guided by a conception of the successful veterinary professional as one capable of navigating and sustainably balancing the (sometimes competing) needs and expectations of multiple stakeholders, the project integrated multiple sources of evidence to derive an employability framework representing the dimensions and capabilities most important to veterinary professional success. This framework provides a useful complement to those based in narrower views of competency and professionalism. One notable difference is its added emphasis on broad success outcomes of satisfaction and sustainability as well as task-oriented efficacy, thus inserting ‘the self’ as a major stakeholder and bringing attention to resilience and sustainable well-being. The framework contains 18 key capabilities consistently identified as important to employability in the veterinary context, aligned to five broad, overlapping domains: veterinary capabilities (task-oriented work performance), effective relationships (approaches to others), professional commitment (approaches to work and the broader professional ‘mission’), psychological resources (approaches to self), plus a central process of reflective self-awareness and identity formation. A summary of evidence supporting these is presented, as well as recommendations for situating, developing and assessing these as learning outcomes within veterinary curricula. Though developed within the specific context of veterinarian transition-to-practice, this framework would be readily adaptable to other professions, particularly in other health disciplines.